Clothes with no emperors: the materiality of digital fashion (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
Digital garments are tailored computationally and dressed virtually. Intended to be displayed rather than worn, digital fashion exemplifies the function of aesthetic commodities as defined by Gernot Böhme: the production of atmospheres – intangible qualities arising from a material encounter – towards the staging of life. Yet, made from pixels instead of fabric, virtual garments beckon a new conceptual framework for the role of materiality in atmospheric productions. Drawing from new media and affect scholars, this essay traces the display of digital garments across three sites: the e-commerce website, social media, and the runway show. By analyzing the visual and literary production surrounding digital fashion, this essay proposes“elemental surface” as a representational technique and rhetorical strategy through which digital garments produce and intensify the body’s affective presence. Situating Böhme’s formulation of atmosphere in dialogue with the notion of“aura” put forth by Walter Benjamin, the study of digital fashion foregrounds the role of environmental perception in the history of haptic technology.
Keywords: Digital fashion; Materiality; Atmosphere; Hapticity; Aesthetic economy